2015
DOI: 10.5455/musbed.20150414123805
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of black stain and dental caries in children attending a university pediatric dentistry clinic in Istanbul

Abstract: Siyah dışsal renkleşmesi olan ve olmayan çocukların sayısı DMF-T ve df-t değerlerine, cinsiyete, ebeveyn eğitim seviyesine ve diş fırçalama sıklığına göre fark göstermedi (p> 0.05). Sonuçlar:Ortalama df-t ve DMF-T değerleri, siyah dışsal renkleşmesi olan ve olmayan çocuklar arasında anlamlı fark göstermedi. Siyah dışsal renkleşme ile df-t ve DMF-T değerleri arasında anlamlı ilişki saptanmadı.Çalışmamıza dahil olan çocuklarda siyah dışsal renkleşme prevalansı literatürdeki Brezilya, İtalya, Almanya, İspanya, Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…This finding is contradictory to the prevalence study done by Akyuz et al ., who had stated that there was no association between the BSs and low caries prevalence. [ 15 ] The current study strongly suggests that there exists a greater diversity in the S. mutans between the caries-active and black tooth stains. The knowledge of this genotypic diversity of S. mutans in BSs and caries-active individuals may help in the development of new treatment strategies for the prevention of these BSs.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This finding is contradictory to the prevalence study done by Akyuz et al ., who had stated that there was no association between the BSs and low caries prevalence. [ 15 ] The current study strongly suggests that there exists a greater diversity in the S. mutans between the caries-active and black tooth stains. The knowledge of this genotypic diversity of S. mutans in BSs and caries-active individuals may help in the development of new treatment strategies for the prevention of these BSs.…”
Section: Discussionmentioning
confidence: 66%
“…Akyuz et al . had reported that there was no relation between black tooth stains and caries activity,[ 15 ] and few studies positively support the low caries prevalence in children with BSs. [ 10 11 16 ] Since there is no complete absence of S. mutans in saliva or plaque of children with BSs,[ 7 17 ] it is imperative to elicit the reason for their low caries activity in children with these BSs.…”
Section: Introductionmentioning
confidence: 99%
“…BS can be observed in both dentitions, primary and permanent, and the prevalence was reported as 1% to 20%, varying according to the country and the population where the study was conducted [7]. However, studies conducted in different countries emphasize that BS formation does not make a significant difference between the sexes [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological studies in this area have shown that patients with BS have a low caries experience [1,8,9,[17][18][19][20]. The studies have showed the caries-reducing effect of black stains by pointing low DMFT value, which is a parameter that measures the total caries experience, missing teeth and restorations of the individual's entire mouth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation